Relationship between Poorly Controlled Asthma and Sleep-Related Breathing Disorders in Children with Asthma: A Two-Center Study - Yun Guo; Xiuqing Zhang; Feng Liu; Ling Li; Deyu Zhao; Jun Qian (Canadian Respiratory Journal)
Objective. Asthma and sleep-related breathing disorders (SRBD) are common chronic respiratory diseases in children. The relationship between asthma and SRDB is bidirectional. However, only a few studies have analyzed the relationship between asthma control status and risk of SRBD. The aim of this study was to evaluate the relationship between asthma control and SRBD and further assess the relationship between therapy/atopy/lung function of children with asthma and SRBD. Methods. A total of 209 children aged 3–16 years were enrolled in this study. Pediatric sleep questionnaire (PSQ) scores were used to identify children at high risk of developing SRBD. Data on asthma control status, therapy, allergy, lung function, and exhaled nitric oxide were collected. Results. A significantly higher risk of SRBD was found among children with poorly controlled asthma (34.25% vs. 13.97%, P < 0.01) and allergic rhinitis (AR) (34.29% vs. 13.92%, P < 0.01) than among children with well-controlled asthma and AR. The prevalence of SRBD was also significantly higher in asthmatic children with obesity than that with just obesity (42.11% vs. 20.00%, P < 0.05). Multiple logistic regression analysis showed that poorly controlled asthma (OR, 2.746 (95% CI, 1.215–6.209); P < 0.05) and poorly controlled AR (OR, 3.284 (95% CI, 1.430–7.544); P < 0.01) increased the odds of having SRBD. Conclusion. Poorly controlled asthma and AR increase the risk of SRBD. A routine check of the level of asthma control and appropriate use of medication for AR are important because of their influence on SRBD.